In pursuit of a 'whole-brain' approach to undergraduate teaching: implications of the Herrmann brain dominance model. Issue 12 (2nd December 2017) - Hughes, Mathew; Hughes, Paul; Hodgkinson, Ian R.
Abstract : The question of 'how we learn' continues to direct scholarly debate, yet undergraduate teaching is typically designed to homogenise the learning environment. This is despite heterogeneous learning outcomes ensuing for students, owing to their different learning styles. Accordingly, we examine the relationship between teaching methodologies and learning styles. Drawing on the Herrmann Brain Dominance Instrument and the theory of 'whole-brain' teaching, we find a suite of teaching methodologies that are generic across learning styles – tutorials, group work, firm-oriented case studies, game playing, reading journal papers, handouts, PowerPoint slides, in-class examples, in-class short exercises, and videos – and find a group of teaching methodologies – lectures, seminars, people-oriented case studies, creative problem-solving, reading textbooks, guest speakers, in-class small group exercises, homework, role-play, problem-based learning, self-directed learning, project-based learning, and class debates – that target and develop specific learning styles. Implications of the 'whole-brain' model for teaching and learning are discussed.